Enterprise and Organizational Modeling and Simulation : 11th International Workshop, EOMAS 2015, Held at CAiSE 2015, Stockholm, Sweden, June 8-9, 2015, selected papers /: 11th International Workshop, EOMAS 2015, Held at CAiSE 2015, Stockholm, Sweden, June 8-9, 2015, selected papers. (2015) - Unknown
No abstract available